Entangled domains: empire, law, and religion in Northern Nigeria - Akande, Rabiat (Cambridge studies in law and society, 2023)
Set in Colonial Northern Nigeria, this book confronts a paradox: the state insisted on its separation from religion even as it governed its multireligious population through what remained of the precolonial caliphate. Entangled Domains grapple with this history to offer a provocative account of secularism as a contested yet contingent mode of governing religion and religious difference. Drawing on detailed archival research, Rabiat Akande vividly illustrates constitutional struggles triggered by the colonial state's governance of religion and interrogates the legacy of that governance agenda in the postcolonial state. This book is a novel commentary on the dynamic interplay between law, faith, identity, and power in the context of the modern state's emergence from colonial processes.